Important features of sustainable aggregate resource management - Šolar, Slavko V. (Geologija, 2004)
Every society, whether developed, developing or in a phase of renewal following governmental change, requires stable, adequate and secure supplies of natural resources. In the latter case, there could be significant need for construction materials for rebuilding infrastructure, industrial capacity, andhousing. It is essential that these large-volume materials be provided in arational manner that maximizes their societal contribution and minimizes environmental impacts. We describe an approach to resource management based onthe principles of sustainable development. Sustainable Aggregate Resource Management offers a way of addressing the conflicting needs and interests of environmental, economic, and social systems. Sustainability is an ethics basedconcept that utilizes science and democratic processes to reach acceptable agreements and tradeoffs among interests, while acknowledging the fundamental importance of the environment and social goods. We discuss the features of sustainable aggregate resource management.
Keywords: civil engineering; gospodarjenje; gradbeništvo; mineralne surovine; nahajališča; sustainable development; trajnostni razvoj